Neuroscientific Foundations of Early Music Education: Enhancing Cognitive, Emotional, and Social Development in Primary Schools - Sánchez, Maria Robles (International Journal of Scientific Research and Management (IJSRM), 2025)
Early music education represents a transformative approach to nurturing the developing brain, offering unique benefits across cognitive, emotional, and social domains in primary school children. Neuroscientific research demonstrates that music activates multiple brain regions simultaneously, stimulating auditory, motor, and prefrontal networks during sensitive periods of neuroplasticity. This engagement strengthens executive functions, working memory, attention, and language acquisition, thereby laying a strong foundation for academic achievement and lifelong learning.Equally important are the emotional benefits of music education. Musical activities have been shown to regulate stress, foster emotional awareness, and enhance resilience by engaging neural systems associated with affective processing and reward. Through structured exposure to rhythm, melody, and harmony, children gain tools for self-regulation and emotional expression, both of which contribute to overall well-being and mental health.The social dimension of music education is equally compelling. Group music-making, such as ensemble performance and collaborative singing, nurtures empathy, cooperation, and prosocial behaviors. These experiences strengthen peer relationships, promote inclusivity, and support the development of essential interpersonal skills. Such outcomes align with broader educational goals of preparing children for active participation in their communities and cultivating a sense of belonging.This paper synthesizes neuroscientific evidence, developmental studies, and educational practices to position early music education as a critical component of holistic child development. It argues that music should not be treated merely as an artistic enrichment, but as a scientifically grounded pedagogical tool. By integrating music programs into primary school curricula, supported by teacher training and policy frameworks, education systems can maximize children’s intellectual growth, emotional resilience, and social connectedness. Ultimately, music education provides an evidence-based pathway to equipping the next generation with skills and capacities vital for success in the twenty-first century.